Initial community response to a novel spatial repellent for malaria prevention in Busia County, Kenya - Sheila Muya Ekodir; Lucy Baker; Julius I. Odero; Jane Klein A. Ikapesi; Moureen Ekisa; Albert Casella; April Monroe; Anna Passaniti; Eric Ochomo; Steven A. Harvey (Malaria Journal)
Abstract Background Malaria transmission in Africa significantly declined between 2005 and 2015 due to widespread distribution of insecticide-treated nets (ITNs). However, since 2015, transmission has increased due to insecticide resistance and biting at times when people are not using ITNs. Spatial repellents (SRs) may help address these challenges. A double-blinded cluster-randomized controlled trial (cRCT) in Busia County, Kenya, reported that Mosquito Shield™, a transfluthrin-based SR, reduced malaria infections by 33.4% during interim analysis and 32.7% by the end of the study, among children aged 6 months to 10 years. Understanding community responses to SRs is critical for their successful deployment and long-term use. This paper reports the initial community response to MosquitoShield™ as part of the Advancing Evidence for the Global Implementation of Spatial Repellents (AEGIS) project. Methods Longitudinal qualitative data were collected from 30 households participating in the cRCT, using modified trials of improved practices (TIPs) to assess participants’ perceptions of MosquitoShield’s utility, efficacy, appearance, and user experience with monthly product replacement. This analysis focuses on initial responses recorded one week and two months post-installation. The data were analysed using thematic coding, with researchers blinded to trial arm assignment. Results The participants reported a positive initial response to the SR, with a significant perceived reduction in mosquito density and activity. Some also reported concerns about the product’s effectiveness over time and its comparison with existing mosquito control methods, particularly after first replacement. Participants highlighted their perception that the SR provided continuous protection in contrast with the situational protection offered by ITNs. Improvement suggestions included modified installation methods plus a longer-lasting product that protected more space. Conclusion MosquitoShield™ shows potential as a promising malaria prevention tool among communities in Busia County, Kenya. Incorporating user feedback and addressing concerns about product installation, duration, and coverage are crucial for successful implementation. Future research exploring community perceptions, cultural factors and behavioural responses related to long-term acceptability and the impact of SRs on malaria transmission will be crucial to ensure effective SR implementation.